Determinación de anticuerpos totales (IgG/IgM) y específicos (IgM) para el virus de la hepatitis E y detección molecular del virus en heces de humanos con o sin exposición ocupacional a porcinos en 10 municipios de Antioquia (2015)
ABSTRACT: In 10 municipalities of Antioquia (Colombia) the positivity rate in serum for total (IgG/IgM) and specific (IgM) antibodies to hepatitis E virus (HEV) was determined, and tests were done for the presence of HEV RNA in the feces of individuals positive for IgM antibodies. According to previous exposure to pigs, two different groups were included, namely: exposed and unexposed. The latter group was subdivided into cohabitants of the exposed ones and general population. The frequency of total anti-HEV antibodies in the exposed group was 15.7%, and that of IgM, 2.5% (p<0.001). In the group of cohabitants, total antibodies were found in 5.9%, while IgM antibodies were not present. In the general population IgG/IgM antibodies were present in 7.2% and IgM, in 0.81% (p<0.001). None of the fecal specimens was positive for HEV RNA. These results indicate that individuals with occupational exposure to pigs have higher risk (RP: 2.42) of being positive for anti-HEV antibodies than the unexposed ones (95% CI: 1.66-3.53) (p<0.001). Also, that in Antioquia HEV is present regardless of the exposure to pigs. Further studies on HEV in Colombia should be done.